Validation of Bioinformatics Software: A Software Quality Engineering Approach - Gopinath Kathiresan (The Bioscan, 2024)
The essential research and clinical implementation fields rely on Bioinformatics software to perform genome sequencing and protein structure prediction tasks. Due to their error-proneness, the tools generate improper biological results. Software Quality Engineering (SQE) practices deliver precise and dependable bioinformatics software through their testing methods unit testing, regression testing, and validation protocols. Bioinformatics depends on thorough software validation because untested programming errors generate wrong genetic data along with inadequate protein models which negatively impacts medical analysis and therapeutic interventions. The document examines SQE practices in bioinformatics software development by showcasing examples between software errors and successful validation methods in actual use. The document pays special attention to essential testing and validation standards because its purpose is to develop guidelines that support better bioinformatics software implementation in both research labs and clinical settings.